2010
DOI: 10.1148/rg.306105517
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Neoplasms of the Kidney in Adults: Imaging Spectrum with Radiologic-Pathologic Correlation

Abstract: Mesenchymal neoplasms of the kidney in adults cover a wide spectrum with characteristic ontogeny and histologic findings and variable biologic profiles and imaging findings. Benign mesenchymal renal tumors include angiomyolipoma, leiomyoma, hemangioma, lymphangioma, juxtaglomerular cell tumor, renomedullary interstitial cell tumor (medullary fibroma), lipoma, solitary fibrous tumor, and schwannoma. Malignant renal tumors of mesenchymal origin include leiomyosarcoma, rhabdomyosarcoma, angiosarcoma, osteosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 46 publications
6
112
1
7
Order By: Relevance
“…The histological differential diagnosis of leiomyoma consists of other benign and malignant renal masses (12,13). Differentiation of leiomyosarcomas from leiomyomas is difficult with imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The histological differential diagnosis of leiomyoma consists of other benign and malignant renal masses (12,13). Differentiation of leiomyosarcomas from leiomyomas is difficult with imaging.…”
Section: Discussionmentioning
confidence: 99%
“…8 With regard to the immunohistochemical study, SFT has been shown to be highly positive for CD34, CD99, and bcl-2, and CD34 has been considered as a specific immune-peroxidase marker for SFT. [10][11][12][13] Other immunohistochemistries involving cytokeratin, SMA, S-100 protein, desmin, CD117 and epithelial membrane antigen are negative, but useful for differential diagnosis of SFT. Therefore, we diagnosed this case as a SFT based on the following histological features: the tumour cells were diffusely and strongly positive for CD34, and a positive expression of bcl-2, CD99 and Caldesmon was also present in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Legritkábban retroperitonealisan (0,8-8,3%) hasi fájdalom vagy érzékeny hasi terime képével jelentkezik [20]. A szervezet bármely régiójában kialakulhat (pajzsmirigy [21], gingiva [22], nyelv [23], mediastinum [24], elülső hasfal [25], vese [26], mellék-vese [27], nyelőcső, cardia, gyomor, proximalis és distalis duodenum, jejunum, ileum, colon [28] és női genitá-liák [29]). MR-vizsgálattal az SS környezetétől élesen elhatároló-dó, nagymértékben cisztikus megjelenést mutat, 20-30%-ban tartalmaz kalcifikációt [30].…”
Section: Megbeszélésunclassified